Therapeutic Potential of Marine Probiotics: A Survey on the Anticancer and Antibacterial Effects of Pseudoalteromonas spp. - Osita C. Eze; Dinebari P. Berebon; Stephen C. Emencheta; Somtochukwu A. Evurani; Chibundo N. Okorie; Victor M. Balcão; Marta M. D. C. Vila (MDPI AG, 2023)
Due to the increasing limitations and negative impacts of the current options for preventing and managing diseases, including chemotherapeutic drugs and radiation, alternative therapies are needed, especially ones utilizing and maximizing natural products (NPs). NPs abound with diverse bioactive primary and secondary metabolites and compounds with therapeutic properties. Marine probiotics are beneficial microorganisms that inhabit marine environments and can benefit their hosts by improving health, growth, and disease resistance. Several studies have shown they possess potential bioactive and therapeutic actions against diverse disease conditions, thus opening the way for possible exploitation of their benefits through their application. Pseudoalteromonas spp. are a widely distributed heterotrophic, flagellated, non-spore-forming, rod-shaped, and gram-negative marine probiotic bacteria species with reported therapeutic capabilities, including anti-cancer and -bacterial effects. This review discusses the basic concepts of marine probiotics and their therapeutic effects. Additionally, a survey of the anticancer and antibacterial effects of Pseudoalteromonas spp. is presented. Finally, marine probiotic production, advances, prospects, and future perspectives is presented.